Halo graphic novel ebook - Faerber, Jay (Dark Horse Comics, LLC., 2021)
Dark Horse Books is proud to present the legendary graphic novel that introduced Halo to the world of comics--back for the first time in over a decade!This book includes four classic Halo stories that expand the deep lore of the Halo universe told by some of the finest creators in comic-book history. Artist Simon Bisley and writer Lee Hammock give us the central tale titled ""The Last Voyage of the Infinite Succor."" Award-winning mangaka Tsutomu Nihei writes and draws a tale of Sgt. Johnson's epic escape in ""Breaking Quarantine"". Ed Lee, Andrew Robinson, and Jay Faerber team up on a story of technology in the 26th century with ""Armor Testing."" Finally, Brett Lewis and the world-renowned artist Jean ""Moebius"" Giraud round out this one-of-a-kind Halo experience with a story that showcases humanity's plight against the Covenant from a unique civilian perspective in ""Second Sunrise Over New Mombasa.""